Colonization with extended-spectrum cephalosporin-resistant Enterobacterales (ESCrE) and carbapenem-resistant Enterobacterales (CRE) in healthcare and community settings in Botswana: an antibiotic resistance in communities and hospitals (ARCH) study. (September 2022) - Mannathoko, Naledi; Mosepele, Mosepele; Gross, Robert; Smith, Rachel M.; Alby, Kevin; Glaser, Laurel; Richard-Greenblatt, Melissa; Dumm, Rebekah; Sharma, Aditya; Jaskowiak-Barr, Anne; Cressman, Leigh; Sewawa, Kgotlaetsile; et al.
Highlights: Extended-spectrum cephalosporin-resistant Enterobacterales (ESCrE) prevalence was high in hospital, clinic, and community settings. Carbapenem-resistant Enterobacterales (CRE) prevalence was high in hospitals. ESCrE and CRE prevalence varied significantly by region and clinical setting. ESCrE and CRE prevalence decreased significantly after a countrywide lockdown. Abstract: Objectives: Although extended-spectrum cephalosporin-resistant Enterobacterales (ESCrE) and carbapenem-resistant Enterobacterales (CRE) are a global challenge, data on these organisms in low- and middle-income countries are limited. In this study, we sought to characterize colonization data critical for greater antibiotic resistance surveillance efforts. Methods: This study was conducted in three hospitals and six clinics in Botswana. We conducted ongoing surveillance of adult patients in hospitals and clinics and adults and children in the community. All participants underwent rectal swab sampling to identify ESCrE and CRE. Results: Enrollment occurred from January 15, 2020, to September 4, 2020, but paused from April 2, 2020, to May 21, 2020, because of a countrywide COVID-19 lockdown. Of 5088 individuals approached, 2469 (49%) participated. ESCrE colonization prevalence was 30.7% overall (43% for hospital participants, 31% for clinic participants, 24% for adult community participants, and 26% for child community participants) ( P <0.001). A total of 42 (1.7%) participants were colonized with CRE. CRE colonization prevalence was 1.7% overall (6.8% for hospital participants, 0.7% for clinic participants, 0.2% for adult community participants, and 0.5% for child community participants) ( P <0.001). ESCrE and CRE prevalence varied substantially across regions and was significantly higher prelockdown versus postlockdown. Conclusions: ESCrE colonization was high in all settings in Botswana. CRE prevalence in hospitals was also considerable. Colonization prevalence varied by region and clinical setting and decreased after a countrywide lockdown.